Experimental studies of vortex flaps and vortex plates - Rinoie, K. (Cranfield University, 1991)
Low-speed wind tunnel tests have been made to investigate the flow around a leading-edge vortex flap at the maximum L/D condition. Tests were also made to measure the performance of the inverted vortex flap and the vortex plate. The force measurements and flow visualization tests were conducted on a 60deg delta wing model. Results indicate that the lift to drag ratio is a maximum for any given flap deflection angle when the flow comes smoothly onto the deflected vortex flap without forming a large leading-edge separation vortex on the flap surface. The benefit of the vortex plate is seen in the drag results which are smaller than those for the datum wing. This benefit is due to some leading-edge suction acting on the forward facing region between the delta wing and the vortex plate.